Potential for impact: ILCA looks to the future - International Livestock Centre for Africa (International Livestock Centre for Africa, 1992)
Presents papers discussing the potential for impacts within ILCA's organisational framework and mandate. The introductory paper raises general issues and poses questions that are pursued in the other papers. These papers address the environmental, economic and social components of impact within the organisation. Case studies on ILCA's research on tenure policy and alley farming, forage legumes, animal traction, milk processing, hay making and studies on pricing policies, technology generation and ILCA's research networks are presented in the papers.